Carbon dioxide-emission in China׳s power industry: Evidence and policy implications. (July 2016) - Yang, Lisha; Lin, Boqiang
Abstract: The Logarithmic Mean Divisia Index (LMDI) and scenario analysis have been applied respectively to analyze the impact of CO2 -emission and its potential reduction in China׳s power industry. According to the results of LMDI, there are six factors that affect the carbon emission in the power industry. Electricity intensity (EI), and economic activity (EA) are the primary driving factors for the increment in emissions, accounting for 42.33% and 57.05% of the total increment during 1985 to 2011. Results also demonstrated that energy efficiency (EE) contributed 13.54% abatement during 1985 to 2011, and will play a key role in emission abatement in the future. Furthermore, the paper estimate the trend of power sector׳s carbon dioxide emission under three scenarios (basic, moderate and optimum) in order to determine the mitigation potential. The potential mitigation rate will equal to 22.03% and 37.57% in 2020 in Case A and Case B respectively in 2020.